Pendekatan Extreme Programming dalam Pengembangan Sistem Informasi Posyandu Berbasis Web - Sori Mahummat Siringo Ringo; Arief Ichwani (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2024)
Posyandu is one of the government's platforms for providing health services to the community. Posyandu plays an important role in monitoring the nutritional development of children under five at the village level. However, due to the unintegrated system, posyandu services and activities have not been running well. Posyandu pasirwaru is a case study in this research, where the services and activities at Posyandu pasirwaru are still carried out manually or using a notebook. Meanwhile, in posyandu data is needed quickly and accurately for a smooth service process. This research aims to design and build a Posyandu application that aims to improve efficiency and accuracy in data management and health services at Posyandu. This application is designed by utilizing the latest technology to facilitate the process of recording, monitoring, and analyzing health data for toddlers and pregnant women. The development method used in this research is the eXtreme Programming method. The final result of the research is testing which shows that the use of this application is able to speed up the process of recording and reporting data, as well as providing easier and faster access to health information. Thus, the design of this Posyandu application is expected to make a positive contribution in improving the efficiency and quality of health services at Posyandu and help make better decisions based on accurate and integrated data.